Mutasi Trichoderma sp. untuk Meningkatkan Sekresi Selulase - W. M., Ali-Mursyid (Fakultas kedokteran Hewan Universitas Airlangga Surabaya, 2007)
This research is aimed to increase cellulase secretion on Trichoderma sp. by mutation method. Trichoderma PK1J2 (5x10(8) spore/ml) was turned into a suspension in utagen solution (400ug/ml ethidium bromide and 0,5 M ethyl methane sulfonate) for 120 minutes. The sreening of mutants which were able to produce hyper cellulase secretion was done by spreading it on a solid medium containing 1% carboxy methyl cellulose as the single carbon source and 15% glycerol as the catabolite repressor. Mutants which were resistant to catabolite repression and produced hyper cellulase secretion would frm larger clear zone than its parent strain after it was flooded by 1% congo red indicator. Mutant AA1, AA2, AB1, AB2, and AC1 were chosen in this screening. The cellulase activity of those five mutants was measured after it was inoculated in liquid medium for 4 days. Cellulase activity measurement was done by using number 1 Whatmann filter paper substrate. From the five mutants, mutant AA1 gave highest cellulase activity. The mutant AA1 and its parent strain were inoculated in liquid medium for 7 days and its cellulase activity was measured every day. The peak of cellulase activity was reached after being incubated for 5 and 7 days for mutant AA1 and its parent strain respectively. The maximum cellulase activity of mutant AA1 was 1.4 times higher than its parent strain. It is concluded that mutation on Trichoderma sp. produces mutant which is resistant to catabolite repression ant is able to produce hyper cellulase secretion.